2019
DOI: 10.1017/s1478951518001062
|View full text |Cite
|
Sign up to set email alerts
|

Distress and self-care among chaplains working in palliative care

Abstract: BackgroundThe prevalence of burnout and distress among palliative care professionals has received much attention since research suggests it negatively impacts the quality of care. Although limited, research suggests low levels of burnout or distress among healthcare chaplains; however, there has been no research among chaplains working in specific clinical contexts, including palliative care.ObjectiveThis study explored the distress, self-care, and debriefing practices of chaplains working in palliative care.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“… 31 The experience of being fully listened to serves as an important therapeutic intervention before any action such as referral to resources or offering of prayer. 31 , 33 …”
Section: Discussionmentioning
confidence: 99%
“… 31 The experience of being fully listened to serves as an important therapeutic intervention before any action such as referral to resources or offering of prayer. 31 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…The correlations between factors (Φ) were evaluated by applying GEOMIN correlations. Reliability was assessed by using the composite reliability (CR) coefficient and Cronbach's α , where values greater than 0.70 were expected (Valentini and Damasio, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Given that healthcare providers working in palliative care commonly deal with contexts of cumulative loss and suffering (Mills et al, 2020), there is a perceived need to expand the knowledge of strategies that can promote personal well-being for these providers. In a study that aimed to explore distress, self-care, and debriefing practices of palliative care workers, results of the multivariate analysis identified that suffering decreased with the increase in self-care (White et al, 2019). The proactive practice of self-care is an important approach to promoting well-being for this population (Beng et al, 2015; Sansó et al, 2015; Adams et al, 2020), although it is not practised widely across it.…”
Section: Introductionmentioning
confidence: 99%
“…Care of self, emotionally, physically, and spiritually, has long been an important aspect of spiritual caregiving and perhaps more so during the challenges to chaplaincy practices that have arisen during the SARS-Cov-19 Pandemic (White et al., 2019). Chaplaincy is a role with high emotional demand and high levels of emotional labor (Hochschild, 1983).…”
Section: Introductionmentioning
confidence: 99%